A Sago Positive Character: A Literature Review - Budhi Setiawan; Fetriyuna Fetriyuna; Sri Murniani Angelina Letsoin; Ratna Chrismiari Purwestri; Ignasius Radix A.P. Jati (Universitas Wijaya Kusuma Surabaya, 2022)
Sago is a carbohydrate-rich food that contains resistant starch. In some parts of Indonesia, Malaysia, and Papua New Guinea, sago is a common staple food. Studies have been performed to elucidate the physicochemical and structural properties of sago starches. The paper's objective is to review potential positive physiological responses to sago-based product consumption from previous records. This study is a literature review of preceding published articles related to sago intake in human subjects’ research. The literature search was performed through databases with assigned keywords combination and then selection of the articles based on the criteria. The outcomes of this review concluded that sago had a lower glycemic index with immediate intestinal absorption. Sago-based products could provide a suitable energy source for sustaining physical performance and promoting faster recovery after exercise. It can be an appropriate alternative as an energy source for active healthy individuals.